(untitled) (International Journal of Innovative Technologies in Economy, 2019)
Investment policy has its peculiarities in agro-industrial complexes. The article analyzes the factors to formation of a favorable investment environment in the food industry, considering combined interests of agricultural, industrial and service organizations, stimulating the investing activity and providing efficiency of investment policy in agro-industrial complexes.